Development strategy of research and production enterprises: types and features - E. A. Pogrebtsova (Омский научный вестник: Серия "Общество. История. Современность")
The problems of forming an enterprise development strategy and its relationship with the factors of the external and internal environment have been studied by many scientists. However, not enough attention has been paid to the essence of strategy formation at scientific enterprises. The article presents an interpretation of the concept of «enterprise strategy» taking into account the features of a scientific enterprise. Special attention is paid to the types of strategies of research and production enterprises. Using the example of an operating enterprise, the stages of forming a strategy based on the use of a system of balanced indicators are shown.